Association between muscle strength and advanced fibrosis in non‐alcoholic fatty liver disease: a Korean nationwide survey. Issue 5 (7th July 2020) - Kang, Sunyoung; Moon, Min Kyong; Kim, Won; Koo, Bo Kyung
Abstract: Background: We investigated the association between muscle strength and the prevalence of advanced fibrosis among individuals with non‐alcoholic fatty liver disease (NAFLD) using a nationwide cross‐sectional survey. Methods: Individuals, 20 to 79 years of age, from the Korean National Health and Nutrition Examination Surveys (KNHANES) from 2014 to 2016 were selected ( N = 14 861), with sample weights applied. Muscle strength was quantified as the handgrip strength divided by the body mass index (BMI); low muscle strength (LMS) was defined as the lowest quartile (Q1 ) of the handgrip strength/BMI for our sample population. NAFLD was defined as hepatic steatosis index >36. Advanced fibrosis was defined as a fibrosis‐4 index score ≥1.30 (FibrosisFIB4 ). Results: The mean age of the study population was 45.6 ± 0.2 years, and 42.4% were male. As muscle strength increased, the mean BMI and age decreased accordingly, and the proportions of diabetes, dyslipidaemia, hypertension, and obesity decreased significantly ( P < 0.001 for all). In a crude analysis, the LMS was associated with an increased prevalence of NAFLD (odds ratio [OR] 3.62, 95% confidence interval [CI] 3.25–4.03, P < 0.001), which remained significant even after adjustment for age, sex, obesity, insulin resistance, diabetes, hypertension, dyslipidaemia, and high‐sensitivity C‐reactive protein (OR 1.66, 95% CI 1.28–2.16, P < 0.001). In this logistic regression model, the prevalence of NAFLD decreased by 24% with each quartile increment in muscle strength (OR 0.76, 95% CI 0.68–0.85, P < 0.001). Among individuals with NAFLD ( n = 2092), LMS was significantly associated with the presence of advanced fibrosis (FibrosisFIB4 ) independently of age, sex, obesity, diabetes, hypertension, dyslipidaemia, and high‐sensitivity C‐reactive protein (OR 1.66, 95% CI 1.01–2.49, P = 0.015), which lost its statistical significance after additional adjustment for insulin resistance. Conclusions: Low muscle strength is independently associated with NAFLD. The significant association between LMS and advanced fibrosis in NAFLD may be mediated through insulin resistance.